2020
DOI: 10.2298/sos2004433d
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic aspect of sodium carbonate mechanical transformations under different environment

Abstract: During mechanical activation, the energy of treated material is raised to a higher level that can lead to the chemical transformation of the activated material. This is the point that should be considered as a phenomenon of the mechanochemical transformations appearing as a result of mechanical activation. Sodium carbonate as a substance that is often subjected to mechanochemical synthesis was mechanically activated in this study. The subject was the monitoring of changes in the physico-chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It is observed that sodium carbonate after being aged for a while enables better absorption of carbon dioxide and moisture from air. As well as, the absorbed amount of gasses is a function of a material activated degree (Djordjević et al, 2020). In this communication we presented a control a change of mass inactivated and activated sodium carbonate aged for 96 hours (relaxation period) in three different environments: in vacuum, carbon dioxide and room conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that sodium carbonate after being aged for a while enables better absorption of carbon dioxide and moisture from air. As well as, the absorbed amount of gasses is a function of a material activated degree (Djordjević et al, 2020). In this communication we presented a control a change of mass inactivated and activated sodium carbonate aged for 96 hours (relaxation period) in three different environments: in vacuum, carbon dioxide and room conditions.…”
Section: Introductionmentioning
confidence: 99%